2011
DOI: 10.1007/s00170-011-3643-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of process parameters on part quality and mechanical properties for DMLS and SLM with iron-based materials

Abstract: Rapid manufacturing is an advanced manufacturing technology based on layer-by-layer manufacturing to produce a part. This paper presents experimental work carried out to investigate the effects of scan speed, layer thickness, and building direction on the following part features: dimensional error, surface roughness, and mechanical properties for DMLS with DS H20 powder and SLM with CL 20 powder (1.4404/AISI 316L). Findings were evaluated using ANOVA analysis. According to the experimental results, build direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(145 citation statements)
references
References 15 publications
(16 reference statements)
7
137
1
Order By: Relevance
“…A similar inverse relationship between scan speed and hardness was also found by Kempen et al [1], Delgado et al [5], and Song et al [11] for several types of material on several AM systems. The lower hardness at the higher scan speed could be the result of insufficient melting of the powder (i.e., the laser travels too fast to thoroughly melt all powder particles).…”
Section: Hardnesssupporting
confidence: 64%
See 2 more Smart Citations
“…A similar inverse relationship between scan speed and hardness was also found by Kempen et al [1], Delgado et al [5], and Song et al [11] for several types of material on several AM systems. The lower hardness at the higher scan speed could be the result of insufficient melting of the powder (i.e., the laser travels too fast to thoroughly melt all powder particles).…”
Section: Hardnesssupporting
confidence: 64%
“…Sun et al found that the density of titanium alloy (Ti-6Al-4V) increased with decreasing scan speed [2]. In their comparative study of two AM systems, Delgado et al observed that while one system resulted in reduced hardness and ultimate tensile strength (UTS) with increased scan speed, the other systems did not result in any significant difference in either hardness or UTS [5].…”
Section: Changing Scan Speedmentioning
confidence: 98%
See 1 more Smart Citation
“…Ranking the parameters in order of importance is critical to limiting the scope of design of experiments (DOE) studies that are a common approach to identifying sets of parameters that optimize material properties such as density. An example of the use of DOE methods to rank parameters is given in the main effects analysis of Delgado et al (2012). It is not unusual for DOEs to include hundreds of samples to reach an optimal set of process parameters, making such investigations time consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison study of different powder grades (three different particle size distribution) also has been demonstrated with the aim of fabrication of high density SS 316L parts [24]. Whilst more work has been reported on how to achieve high density parts [25,26], there are few studies that discuss how to achieve such porous parts. Such examples include the work conducted by Cijun et.…”
Section: Introductionmentioning
confidence: 99%